Сильноточные бетатроны - Воробьев А. А. Александр Акимович; Москалёв В. А.; Скворцов Ю. М.; Окулов Б. В.; Шестаков В. Г.; Гончаров В. Я.; Шашов В. В.; Слупский А. М. (1966, 1966)
В фонде НТБ ТПУ отсутствует